Biometric parameters of plants and maize (Zea mays L.) productivity depending on sowing period - Hanhur, V.; Rudenko, V. (Scientific Progress & Innovations, 2023)
Due to the increasing demand for corn grain, there is an important necessity to improve existing and develop new agrotechnical methods aimed at maximizing the genetic potential of crop productivity. Studies conducted during 2021‒2022 at the Poltava State Agricultural Research Station named after M. Vavilov revealed that seedlings of corn hybrids more actively appeared at late sowing dates (May 10), and at the average date ‒ with a one-day time delay. According to the results of seed germination, it was found that in maize hybrids of different maturity groups, it increased to the maximum during the period from early to medium sowing. The studies revealed that the early-maturing hybrid Kvitnevyi 187 MV and the mid-maturing hybrid Bystrytsia 400 MV had the highest plant height at the third sowing date and the mid-early hybrid Orzhytsia 237 ‒ at the middle sowing date. Experimental results showed that the linear sizes of plants of later maturity maize hybrids are less responsive to the time of sowing. The results of the research showed that on average for two years, the yield of the early-maturing corn hybrid Kvitnevyi 187 MV was maximum at the second sowing date (7.19 t/ha). The yield increase over the first and third sowing dates was 0.35 and 0.22 t/ha or 5.1 and 3.2 %, respectively. The yield of the medium-early hybrid Orzhytsia 237 MV was almost the same for both the first and second sowing periods (7.25 and 7.27 t/ha, respectively), the difference was only 0.02 t/ha. In the case of late sowing, a significant reduction in yield was observed (by 0.23 and 0.25 t/ha) in comparison with the early and middle terms, respectively. The mid-season hybrid Bystrytsia 400 MV responded to the time of sowing most strongly. The highest yield (8.05 t/ha) was obtained when it was sown on April 20. At the second and third sowing dates, compared to the first, a significant decrease in grain productivity of the hybrid was noted, by 0.62 and 1.22 t/ha or 8.3 and 17.9 %, respectively, which indicates that its plants are not adaptive enough to the more extreme weather conditions of the summer growing season.